Older Adults in the United States and COVID-19: A Qualitative Study of Perceptions, Finances, Coping, and Emotions - Goins, R. Turner; Anderson, Elizabeth; Minick, Hannah; Daniels, Heather (Frontiers in Public Health, 2021)
Introduction: Older adults have the poorest coronavirus (COVID-19) prognosis with the highest risk of death due to complications, making their COVID-19 experiences particularly important. Guided by the stress-appraisal-coping theoretical model, we sought to understand COVID-related perceptions and behaviors of older adults residing in the United States. Materials and Methods: We used convenience sampling to recruit persons with the following inclusion criteria: Aged ≥ 65 years, English fluency, and U.S. residency. Semi structured in-depth interviews were conducted remotely and audio recorded between April 25, 2020 and May 7, 2020. Interviews were professionally transcribed with a final study sample of 43. A low-inference qualitative descriptive design was used to provide a situated understanding of participants' life experiences using their naturalistic expressions. Results: The mean age of participants was 72.4 ± 6.7. Slightly over half were female (55.8%), 90.6% were White, and 18.6% lived alone. The largest percentages of participants resided in a rural area (27.9%) or small city (25.6%). We identified four themes, including (1) risk perception, (2) financial impact, (3) coping, and (4) emotions. Most participants were aware of their greater risk for poor COVID-19 outcomes but many did not believe in their increased risk. Financial circumstances because of the pandemic varied with largely no financial impacts, while others reported negative impacts and a few reported positive impacts. Coping was problem- and emotion-focused. Problem-focused coping included precautionary efforts and emotion-focused coping included creating daily structure, pursuing new and/or creative activities, connecting with others in new ways, and minimizing news media exposure. Overall, emotional health was negatively affected by the pandemic although some participants reported positive emotional experiences. Conclusions: Perceiving themselves as high risk for COVID-19 complications, older adults used precautionary measures to protect themselves from contracting the virus. The precautionary measures included social isolation, which can negatively affect mental health. Older adults will need to be resourceful and draw on existing resources to cope, such as engaging in creative activities and new strategies to connect with others. Our findings underscore the importance of the preservation of mental health during extended periods of isolation by taking advantage of low-to-no-cost existing resources.